Primary Common Iliac Artery Angiosarcoma With Multiple Bone Metastases Revealed by Dual-Time Point FDG PET/CT Imaging. (March 2019) - Wang, Renjie; Wang, Xueju; Ji, Bin; Guan, Qingtao; Chen, Bin
Abstract : Abstract: Iliac artery angiosarcoma is rare, and bone metastasis as its presenting initial symptom is extremely rare. A 67-year-old man with a history of low back pain presented with multiple MRI-identified lumbar and sacrum lesions highly suggestive of bone metastasis. On subsequent PET/CT scan, in addition to multiple vertebrae and pelvis hypermetabolism, a lesion with intense focal uptake was discovered within the lumen of left common iliac artery. Dual-time point quantitative analysis revealed that the lesion-to-liver ratio of SUVmax was significantly increased in the delayed phase. Biopsy confirmed the lesion as a primary iliac artery angiosarcoma.